(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This article examines the effectiveness of using the Simfox simulator to improve cadets’ efficiency in analyzing X-ray images at a customs institute. Results show analysis time reduced to 9–13 seconds and detection accuracy increased from 20–30 % to 85–100 %.